2021
DOI: 10.1164/rccm.202008-3266oc
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in Adult Patients with COVID-19. Prevalence and Risk of Severe Disease

Abstract: Rationale: Health outcomes of people with coronavirus disease (COVID-19) range from no symptoms to severe illness and death. Asthma, a common chronic lung disease, has been considered likely to increase the severity of COVID-19, although data addressing this hypothesis have been scarce until very recently.Objectives: To review the epidemiologic literature related to asthma's potential role in COVID-19 severity.Methods: Studies were identified through the PubMed (MEDLINE) and medRxiv (preprint) databases using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 123 publications
1
66
1
3
Order By: Relevance
“…In a study in South Korea, the prevalence of asthma among Covid-19 patients was 2.9% [36], somewhat similar to another review which finds that asthma is a pre-morbid condition in about 1.6% of the Covid-19 patients [37]. Another systematic review of the link between asthma and Covid-19 finds a somewhat higher prevalence of asthma among Covid-19 patients (7.46%) [38] echoing the heterogeneity of prevalence across different countries and regions as reported in another systematic review [39].…”
Section: Covid-19 and Asthmasupporting
confidence: 78%
“…In a study in South Korea, the prevalence of asthma among Covid-19 patients was 2.9% [36], somewhat similar to another review which finds that asthma is a pre-morbid condition in about 1.6% of the Covid-19 patients [37]. Another systematic review of the link between asthma and Covid-19 finds a somewhat higher prevalence of asthma among Covid-19 patients (7.46%) [38] echoing the heterogeneity of prevalence across different countries and regions as reported in another systematic review [39].…”
Section: Covid-19 and Asthmasupporting
confidence: 78%
“…Other studies did not provide clear evidence of increased risk of COVID-19 severity, hospitalization, or mortality in asthmatic patients. [29][30][31] The data on SCSs in asthma and COVID-19 are scarce. The results of the Randomized Evaluation of Covid-19 Therapy (RECOVERY) trial 32 showed that oral or intravenous administration of dexamethasone significantly reduces 28-day mortality among patients admitted to hospital with COVID-19 receiving invasive mechanical ventilation or oxygen, whereas Williamson et al 16 using the OpenSAFELY platform to examine factors associated with COVID-19-related death reported that severe asthma defined by recent SCS use was associated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The regional asthma comorbidity rates were estimated as follows: East Asia and the Pacific, 2.2%; Europe, 6.4%; Latin America and the Caribbean, 3.5%; the Middle East and North Africa, 4.9%; North America, 10.2% [44]. Very recently, Terry et al performed a systematic review and meta-analysis of 150 studies and did not find clear evidence of increased risk of COVID-19 diagnosis in asthmatics [45].…”
Section: Susceptibility Of Patients With Asthma To Covid-19 Infectionmentioning
confidence: 99%